Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1590/s0102-09352007000400001
|View full text |Cite
|
Sign up to set email alerts
|

Fate of non O157 Shiga toxigenic Escherichia coli in composted cattle manure

Abstract: To determine the fate of Shiga toxigenic Escherichia coli (STEC) non-O 157 in composted manure from naturally colonized cattle, fresh manure was obtained from three cows carrying non-O157 STEC strains possessing the stx2 gene. Two composting systems were used: a 0.6m deep cave opened in the soil and an one meter high solid manure heap in a pyramidal architecture. Every day, for the 10 first days, and every five days for a month, one manure sample from three different points in both systems was collected and cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 31 publications
1
7
0
5
Order By: Relevance
“…Temperatura baixa durante curto período de tempo pode não ser suficiente para higienizar o composto final. Dessa forma, seu uso como adubo pode levar a contaminação do alimento que será produzido e consequentemente contribuir para disseminação de doenças na propriedade (Gonçalves & Marin, 2007). No início do processo de compostagem, foi observado elevado NMP.g -1 , que sofreu drástica redução durante a compostagem a ponto de não ser mais detectada a presença de coliformes totais e termotolerantes ao final do processo (Tabela 4).…”
Section: Resultsunclassified
“…Temperatura baixa durante curto período de tempo pode não ser suficiente para higienizar o composto final. Dessa forma, seu uso como adubo pode levar a contaminação do alimento que será produzido e consequentemente contribuir para disseminação de doenças na propriedade (Gonçalves & Marin, 2007). No início do processo de compostagem, foi observado elevado NMP.g -1 , que sofreu drástica redução durante a compostagem a ponto de não ser mais detectada a presença de coliformes totais e termotolerantes ao final do processo (Tabela 4).…”
Section: Resultsunclassified
“…The composting process helps to ensure the hygiene of the final compost product (Pourcher et al, 2005;Murkherjee et al, 2006;Gonçalves and Marin, 2007). Previous studies have shown a long-term survival of more than 21 months for E. coli O157:H7 in manure held under a variety of environmental conditions (Kudva et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The use of probiotic strains to supplement the ration of livestock (Lema et al, 2001;Chaucheyras-Durand et al, 2010) and the use of composting to decrease the population of pathogenic microbes (Pourcher et al, 2005;Murkherjee et al, 2006;Gonçalves and Marin, 2007) have both been reported as efficient alternatives to decrease the spread of pathogenic strains on a farm. However, these studies were done separately, and there is little information about the combined use of the two practices to decrease the STEC population present on a sheep farm.…”
Section: Introductionmentioning
confidence: 99%
“…Em um sistema que envolveu o tratamento de dejetos de bovino por compostagem com a presença de Escherichia coli Shigatoxigênica, o sistema foi capaz de eliminar o micro-organismo diminuindo o risco de contaminação ambiental e a disseminação do patógeno (GONÇALVES; MARIN, 2007).…”
Section: Introductionunclassified